Migration in the Mediterranean : mechanisms of international cooperation - Ippolito, Francesca
"The Mediterranean Sea has always been a route for migration. For centuries caravans have crossed its waters for the most diverse reasons: commerce, war, pilgrimage, cultural exchange, etc. In the last decades, these same waters constitute the scenery of what appears as a never ending tragedy, irregular migration and the thousands of related deaths. According to the United Nations High Commissioner for Refugees (UNHCR) and the International Organization for Migration (IOM), 2014 has been so far the deadliest year for the Mediterranean, with nearly 1,900 migrants lost their lives, compared to the 700 recorded in 2013 and about 500 recorded in 2012"--